Stabilised the perovskite cathode for solid oxide fuel cell by surface modification - Khairul 'Izzat Bin Azmi (Nanyang Technological University, 2023)
This research study aims to suppress Strontium (Sr) segregation and stabilise perovskite oxide Sr2Fe1.5Mo0.5O6-δ (SFMO) cathode on Solid Oxide Fuel Cell through surface modification; Atomic Layer Deposition (ALD) of ZrO2 and Infiltration methods. The preparation of SFMO was made through solution combustion synthesis with the electrolyte of the SOFC being LSGM. ALD deposited ZrO2 was done with the use of Plasma-enhanced ALD using TEMAZr as the precursor for 50 and 150 cycles. For infiltration, 2 samples were made which consists of Hf + cations and La2NiO4+δ (LNO) which were deposited on the surface of the cathode. The cell morphology of pristine SFMO and ALD deposited ZrO2 was analysed with the use of FESEM and TEM. Using EIS to garner the cell’s results, comparing between pristine and both ALD cycles, the ALD cycles have shown to degrade slower. The initial polarisation resistance (Rp) of the 50-cycles ZrO2-SFMO is larger than both the pristine SFMO and 150-cycles ZrO2- SFMO. Though for both ALD cycles, its degradation slowed tremendously to almost a constant line after long hours. This degradation cannot be seen in infiltration as both infiltration samples degrade in a linear relationship with time since its Rp increases linearly with time. However though, the degradation of the infiltration is slower than the pristine SFMO and the first 35 hours of 50-cycles ZrO2-SFMO. The best results came from the 150-cycles ZrO2-SFMO.